Implications of Transfer Pricing on MSMEs in the Digital Era - Fitriana, Nur; Sari, Nasya Paramiya; Putri, Natasha Nadira; Adinda, Zahra (Journal of International Accounting, Taxation and Information Systems, 2025)
In the ever-evolving digital era, MSMEs face new challenges and opportunities in managing business transactions, including the implementation of transfer pricing strategies. This research aims to provide a description of how transfer pricing strategies can affect the economy, especially MSMEs, in the digital era. This research method uses a qualitative approach. Data were analysed thematically and tested for validity through triangulation to provide a comprehensive picture of the challenges and solutions for MSMEs in implementing transfer pricing. The result of this study is that transfer pricing, while often used by large companies to shift profits to lower-tax countries, also presents challenges for MSMEs in the digital era. MSMEs face difficulties in implementing appropriate transfer pricing policies due to limited resources, knowledge, and access to technology, but digitalisation offers opportunities to manage transactions more transparently and efficiently to ensure compliance with global tax regulations. Although transfer pricing is often associated with large enterprises, MSMEs also need to understand and manage this policy carefully, especially in the increasingly globalised digital era. Technology allows MSMEs to connect with international markets, but it also brings risks related to complex taxes and regulations. Therefore, it is important for MSMEs to have a clear understanding of transfer pricing, use the right technology, and consult with tax experts in order to comply with regulations and avoid legal issues.